Movement coordination patterns in triple jump training drills - Wilson, C.; Simpson, S.; Hamill, J. (Journal of Sports Sciences, 2009)
The aim of this study was to determine the effectiveness of training drills in replicating the lower extremity coordination patterns used during the triple jump. Three-dimensional kinematic data and synchronized ground reaction force data were collected during the hop-step transition of a triple jump and four related training drills. Relative motion plots and a modified version of the vector coding technique were used to quantify the coordination patterns of the lower extremities. Differences were observed in the coordination patterns between the triple jump and static drills, but not between the triple jump and dynamic drills, and these differences were mainly in the swing (free) leg. The results of this study suggest that if the primary purpose of the training drills is to replicate the movement patterns used in the triple jump, then dynamic drills are more effective than static drills. In addition, coaches should focus on the use of the free leg during these training drills so that the coordination patterns more closely replicate the triple jump. Finally, to provide a more holistic evaluation of training drills, future studies should investigate the similarity of the physical and musculoskeletal demands of jumps and drills.